Localization of Ectopic Mediastinal Parathyroid Adenomas Using Indigo Carmine Injection for Surgical Management: A Preliminary Report - Kammori, Makoto; Kanazawa, Shinsaku; Ogata, Hisae; Kanda, Natsuki; Nagashima, Takashi; Kammori, Mahiro; Ogawa, Toshihisa (Frontiers in Surgery, 2022)
An ectopic parathyroid adenoma (EPA) is a rare entity. The aim of this study was to report our experience in the preoperative localization and surgical management of EPAs. This was a multicenter retrospective study involving patients diagnosed with an EPA (3 males and 7 females) from January 2005 to November 2021. The clinical features, preoperative management, and surgical procedures were analyzed. A cervical neck ultrasound was performed in all patients and showed a focus in 8 patients. Cervicothoracic enhanced computed tomography was performed in all patients and showed a focus in 9 patients. 99mTc-MIBI scintigraphy was performed in 8 patients and showed uptake in 6. We performed a neck dissection and thoracotomy in 1 patient, a thoracoscopy in 1 patient, surgery with a focused approach in 7 patients, 4 of whom were injected with indigo carmine blue, and surgery with a bilateral approach in 1 patient. One hour following the parathyroidectomy, the parathyroid hormone concentration was decreased to 40%-80% of the baseline value. Establishing a preoperative diagnosis of an EPA is challenging for the surgeon, despite progress in the morphologic assessment. Intraoperative parathyroid hormone assay and injection of indigo carmine have been shown to be valuable tools in the appropriate surgical management of an EPA.